2021
DOI: 10.24191/ajue.v17i1.12625
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fuzzy Delphi Technique Towards Designing and Developing the Elements for the e-PBM PI-Poli Module

Abstract: Along with the wave of the Industrial Revolution 4.0 era, shifts in the aspects of approach in teaching and the integration of learning technology should always be given careful research and planning. Therefore, this study aims to see the elements needed to integrate technology and delivery strategies to design and develop an online problem-based learning module for the Islamic Studies course (e-PBM PI-Poli) in Polytechnic. The design of this study is a quantitative study using the Fuzzy Delphi technique. A qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…Several authors (Hasson et al, 2000;Dawood et al, 2021) highlighted that purposive sampling is the best method to do FDM. Finally, we used Microsoft Excel software to analyse and assess experts' perspectives, as Mohamed Yusoff et al (2021) suggested. Figure 2 shows the proposed research framework and how to do it step-by-step.…”
Section: Sample Size and Sampling Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several authors (Hasson et al, 2000;Dawood et al, 2021) highlighted that purposive sampling is the best method to do FDM. Finally, we used Microsoft Excel software to analyse and assess experts' perspectives, as Mohamed Yusoff et al (2021) suggested. Figure 2 shows the proposed research framework and how to do it step-by-step.…”
Section: Sample Size and Sampling Methodsmentioning
confidence: 99%
“…For this purpose, we used the literature review to develop a research questionnaire. Literature reviews, pilot studies, and experience can provide helpful information for developing questionnaire items (Mohamed Yusoff et al , 2021). This research focussed on Kish Island (as a unit of analysis).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Fuzzy Delphi Method (FDM) was developed to overcome this problem through the combination of fuzzy theory and the classical methodology [3][4][5][6][7][8][9]. In general, FDMs usually use linguistic variables in designing the questionnaires to gather opinions from experts and, after that, they consider a defuzzification step; that is, a step in which linguistic labels (or fuzzy numbers) are reduced to real numbers.…”
Section: Introductionmentioning
confidence: 99%